Dorzolamide Chlorhydrate versus Acetazolamide in the Management of Chronic Macular Edema in Patients with Retinitis Pigmentosa: Description of Three Case Reports. (January 2014) - Pacella, Elena; Arrico, Loredana; Santamaria, Valentina; Turchetti, Paolo; Carbotti, Maria Rosaria; La Torre, Giuseppe; Pacella, Fernanda
Aims: To assess the efficacy of topical dorzolamide for treating cystoid macular edema in patients with retinitis pigmentosa and minimize the secondary effects of maintenance therapy in patients with retinitis pigmentosa (RP) who present with chronic microcystic macular edema. Methods: To replace acetazolamide systemic treatment, with a topical treatment using 2% dorzolamide in three patients. The methods performed were OCT scan with a Spectralis HRA-OCT, for the measurement of macular thickness and morphology; best corrected visual acuity was assessed using Early Treatment Diabetic Retinopathy Study (ETDRS), was assessed slit-lamp biomicroscopy, ocular tonometry, fundus biomiocrosopy, and color fundus photography. This therapeutic protocol has been applied and described in three patients. Results: In all three tested patients, following the administration of dorzolamide in eye drop, we observed a remarkable decrease in macular edema, almost comparable to that obtained with acetazolamide per os. Conclusion: The study confirms the anti-edematogenic effect of topical dorzolamide in RP with recurring macular cysts, as this can have a favorable response with topical dorzolamide. In all the three examined patients, the instillation of topical dorzolamide caused a remarkable reduction in their macular edema, as highlighted on OCT.